Formation of management culture of the head of an educational institution: Dialogue technologies and moral guidelines - Oksana Tovkanets (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The article deals with the problem of the use of dialogue technologies in the formation of management culture of the head of an educational institution. It is noted that managerial culture as a component of the professional activity of the head of an educational institution is characterized by peculiarities of awareness of the behavior and activities of people in the organization and is an element of the culture of work, culture of professional activity. It is noted that in high school dialogue technologies that allow in a special way to demonstrate the moral meaning and the meaning of values and provide the basis for their deep consideration are actual. It was emphasized that the dialogue technology includes a sequence of stages that allow to realize the main tasks of the dialogue: a deep analysis of the problem, understanding of its value-semantic and moral content, development of dialogue culture. An intellectual dialogue (deep understanding of the essence of the problem, a high level of moral culture of dialogue interaction); intellectual-based dialogue (involves participants in the search for value meanings, in the process of identifying the system of individual value orientations), reflexive dialogue (allows you to evaluate your own potential and define lines of feedback participants - the leader), motivational dialogue (revealing of interest both to the problem and to the dialogue technology itself), self-actualizing dialogue (appointment - full presentation itself) and others have been marked out. The education of the head of the educational institution in the atmosphere of dialogue and cooperation is much more effective, since the dialogue provides equal conditions for all participants in the educational process, and spiritually-oriented communication contributes to the development of the individual and the realization of the potential of not only students, future leaders of educational institutions, but also of a teacher. It is concluded that the features of the dialogue lead to its definition as a technique of a deep and adequate understanding of the personality, assistance in solving psychological problems, stimulation of the desired changes. The dialogue technologies are aimed at creating conditions for the individual to learn the cultural experience, moral guidelines, social norms of the past and the present; for the formation and development of social qualities of the individual, which will promote professional development, for self-determination and self-actualization of the individual.